THE EFFECT OF DIGITAL MARKETING AND LEARNING ORIENTATION ON MARKETING PERFORMANCE: MEDIATING COMPETITIVE ADVANTAGE - Ardy Fimansyah; M. Taufiq Noor Rokhman; Novita Rifaul Kirom (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study examines how digital marketing, market orientation, and competitive advantage enable batik MSMEs in Proppo Sub-District, Pamekasan Regency, enhance their marketing performance using a resource-based viewpoint. The research population, which was chosen using a census sampling technique, consists of 59 MSME batik business players who use digital marketing. The data was analysed using partial least squares (PLS) modelling of variance-based structural equations. The results show that digital marketing and market orientation greatly increase competitive advantage, which enhances marketing performance.